Leveraging the role of nanotechnology to tackle SSIs in post-operative Breast cancer - Anwesha Kanungo; Sarbari Acharya (Next Nanotechnology)
Surgical site infections (SSIs) in breast cancer patients are a serious clinical problem, frequently caused by biofilms built up by opportunistic microorganisms like Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Staphylococcus aureus and more. Biofilms increase bacteria resistance to drugs and impair immunological response, complicating infection control. Conventional therapies, such as systemic antibiotics, have limited effectiveness due to low biofilm penetration, an increased risk of antimicrobial resistance, and adverse reactions. These disadvantages highlight the critical need for novel techniques to treat SSIs successfully. Recent advances in nanotechnology have emphasized the potential of plant-derived nanoparticles (NPs) as an alternative therapeutic method. These plant extract-derived nanoparticles have excellent antibacterial and antibiofilm characteristics, which can be linked to their bioactive phytochemical content. Furthermore, their biocompatibility, eco-friendliness, and capacity to target biofilm-embedded bacteria make them a suitable choice for treating SSI in breast cancer patients. For the treatment of infections associated with biofilms, plant-based nanoparticles offer a more robust and durable solution. To demonstrate the safety and clinical efficiency of plant-based nanoparticles, further in vivo investigation is expected. This review explores the processes of biofilm development in SSIs, the limits of existing therapies, and the potential of plant-based nanoparticles as an effective and sustainable therapeutic alternative. The introduction of these nanoparticles is an important step toward combating antibiotic resistance and improving outcomes for breast cancer patients with SSIs.